2020
DOI: 10.1177/1078155220907129
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of healthcare workers’ exposure to cyclophosphamide, ifosfamide, methotrexate, and 5-fluorouracil by 24-h urine assay: A descriptive pilot study

Abstract: The objective of this pilot study was to determine the frequency of urination and the concentration of four hazardous drugs (cyclophosphamide, ifosfamide, methotrexate, and fluorouracil) in workers' 24-h urine samples in relation to exposure to traces with hazardous drugs. Methods: The study was conducted in three healthcare centers in the region of Montr eal, Quebec, Canada. We recruited healthcare workers (nurses and pharmacy technicians) assigned to the hematology-oncology department. Each participant was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(58 reference statements)
1
7
1
Order By: Relevance
“…Among those, 37.8% and 33.3% presented internal contamination with CPA and IP, respectively, with the highest median concentration close to the LOQ of the analytical methods. Conversely to the above-mentioned results, other studies failed to detect any concentration of CPA and IP in exposed healthcare workers [ 10 , 13 , 32 , 38 , 40 , 41 , 44 , 45 ]. When biological monitoring was performed on two Belgian pharmacy technicians engaged in CPA preparation with the aid of a robotic system and without appreciable occupational exposure, undetectable levels of CPA could be retrieved in the 24-h urine samples [ 13 ].…”
Section: Resultscontrasting
confidence: 74%
See 4 more Smart Citations
“…Among those, 37.8% and 33.3% presented internal contamination with CPA and IP, respectively, with the highest median concentration close to the LOQ of the analytical methods. Conversely to the above-mentioned results, other studies failed to detect any concentration of CPA and IP in exposed healthcare workers [ 10 , 13 , 32 , 38 , 40 , 41 , 44 , 45 ]. When biological monitoring was performed on two Belgian pharmacy technicians engaged in CPA preparation with the aid of a robotic system and without appreciable occupational exposure, undetectable levels of CPA could be retrieved in the 24-h urine samples [ 13 ].…”
Section: Resultscontrasting
confidence: 74%
“…In fact, while 3.9% of samples collected from the work surfaces of the cytostatic preparation and administration units of an Italian hospital had positive results, among 398 healthcare workers with 24-h urine collection, no traces of ADs, including CPA and IP, could be detected. Comparably, Palamini et al [ 32 ] showed no traces of CPA and IP in the 24 h-urine of 18 nurses and pharmacy technicians assigned to the hematology-oncology departments of three Canadian healthcare centers. These results corroborate those previously obtained from 101 workers at the same departments, where no detectable urinary CPA levels could be determined [ 44 ].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations